Power law profiles in thermally stratified shear flows - Chuang, Hsing, author; Cermak, J. E. (Jack E.), author; Fluid Dynamics and Diffusion Laboratory, College of Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1969)
A "power law'' model is used to describe the wind and temperature profiles in thermally stratified shear flows for bulk Richardson numbers from - 0.8 to 0.2. It is shown that the power of wind and temperature profiles were not independent of the thermal stability and that similarity between wind and temperature profiles is good. Functional dependence of the power upon the thermal stability is shown for data of Prairie Grass and laboratory measurements.
CER69-70-HC-JEC-19.
December 1969.
Prepared for U.S. Army Research Grant DA-AMC-28-043-65-G20.
Keywords: Stratified flow; Shear flow